Status Analysis and Future Development Planning of Fitness APP Based on Intelligent Word Frequency Analysis. (25th May 2022) - Wang, Siqiu; Wang, Shengze
Abstract : In order to analyze the current situation analysis and future development plan of fitness APP, this paper analyzes the current situation of fitness APP combined with the intelligent word frequency analysis algorithm. In order to deal with the problem that the existing qPMS algorithm is very time-consuming to discover motifs in the large DNA sequence dataset D, a structural motif discovery algorithm for large DNA sequence datasets, SMS, is proposed. Moreover, this paper performs motif discovery by mining substrings with high frequency in the input sequence. Through data research, it can be seen that the fitness APP based on intelligent word frequency analysis proposed in this paper has good results. On this basis, this paper analyzes the problems existing in the existing fitness APP and provides suggestions for its future development.